Colour matching in an orb‐web spider: a twig‐masquerading species as seen by potential predators. (28th May 2018) - Xavier, G. M.; Brito, V. L. G.; Gonzaga, M. O.
Abstract: Distinct predator groups perceive prey colour and brightness differently because they harbour distinct visual systems. Therefore, the evaluation of the presence of visual‐based mechanisms of action in defensive strategies must be assessed from the perspective of the visual abilities of potential predators. Wixia abdominalis O.P. Cambridge, 1882 (Araneae, Araneidae) is a masquerader species that imitates its substrate, the twigs of trees. Using reflectance spectrophotometry and colour visual models, we tested and subsequently corroborated the hypothesis that colour matching occurs in this species based on how it is perceived by the primary spider predators, hymenopterans and birds. These results provide a theoretical basis on the role of colour and brightness in this defensive strategy, indicating that susceptibility to the two main groups of spider predators can be influenced by these characteristics. Then, we discussed the causes and implications of this defensive strategy in W. abdominalis and similar spider species. Abstract : Using reflectance spectrophotometry and visual modelling, we tested and subsequently corroborated the hypothesis that colour matching occurs in Wixia abdominalis, a masquerader species, based on how it is perceived by the primary spider predators, hymenopterans and birds. These results provide a theoretical basis on the role of colour and brightness in this defensive strategy, indicating that susceptibility to the two main groups of spider predators can be influenced by these characteristics. We discuss the causes and implications of this defensive strategy in W. abdominalis and similar spider species.